2019
DOI: 10.1210/clinem/dgz247
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Strength, Size, and Composition Following 12 Months of Gender-affirming Treatment in Transgender Individuals

Abstract: Context As many sports are divided in male/female categories, governing bodies have formed regulations on the eligibility for transgender individuals to compete in these categories. Yet, the magnitude of change in muscle mass and strength with gender-affirming treatment remains insufficiently explored. Objective This study explored the effects of gender-affirming treatment on muscle function, size, and composition during 12 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
75
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(102 citation statements)
references
References 34 publications
6
75
0
6
Order By: Relevance
“…Including Gooren and Bunck [62], 12 longitudinal studies [53,[63][64][65][66][67][68][69][70][71][72][73] have examined the effects of testosterone suppression on lean body mass or muscle size in transgender women. The collective evidence from these studies suggests that 12 months, which is the most commonly examined intervention period, of testosterone suppression to femaletypical reference levels results in a modest (approximately − 5%) loss of lean body mass or muscle size (Table 4).…”
Section: Muscle and Strength Metricsmentioning
confidence: 99%
“…Including Gooren and Bunck [62], 12 longitudinal studies [53,[63][64][65][66][67][68][69][70][71][72][73] have examined the effects of testosterone suppression on lean body mass or muscle size in transgender women. The collective evidence from these studies suggests that 12 months, which is the most commonly examined intervention period, of testosterone suppression to femaletypical reference levels results in a modest (approximately − 5%) loss of lean body mass or muscle size (Table 4).…”
Section: Muscle and Strength Metricsmentioning
confidence: 99%
“…This helps to explain the positive correlations between LDCA and gender, serum creatinine, and PT-INR. LDCA may be more likely to occur in female patients because, on average, men have more muscle mass than women, allowing for more citrate metabolism in muscle cells 22 . As serum creatinine is a marker for renal function, it is expected that both citrate and serum creatinine levels will be high if metabolism in the kidneys is slowed.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have addressed the effects of androgen deprivation therapy and GAT in transwomen [18][19][20][21][22] and transmen [20,[22][23][24]. Loss of muscle mass has been shown in transwomen [19][20][21][22] and gains in muscle mass have been shown in transmen [20,22]. Early studies showed that gonadal suppression in men resulted in decreased muscular strength [18], however, a more recent study showed that transwomen had no change in muscle strength [22].…”
Section: Introductionmentioning
confidence: 99%